Transcription of antisense RNA leading to gene silencing and methylation as a novel cause of human genetic disease. - Tufarelli, C; Stanley, J; Garrick, D; Sharpe, J; Ayyub, H; Wood, W; Higgs, D (2003)
Nearly all human genetic disorders result from a limited repertoire of mutations in an associated gene or its regulatory elements. We recently described an individual with an inherited form of anemia (alpha-thalassemia) who has a deletion that results in a truncated, widely expressed gene (LUC7L) becoming juxtaposed to a structurally normal alpha-globin gene (HBA2). Although it retains all of its local and remote cis-regulatory elements, expression of HBA2 is silenced and its CpG island becomes completely methylated early during development. Here we show that in the affected individual, in a transgenic model and in differentiating embryonic stem cells, transcription of antisense RNA mediates silencing and methylation of the associated CpG island. These findings identify a new mechanism underlying human genetic disease.